The first reported outbreak of equine herpesvirus myeloencephalopathy in New Zealand. Issue 2 (3rd March 2016) - McFadden, AMJ; Hanlon, D; McKenzie, RK; Gibson, I; Bueno, IM; Pulford, DJ; Orr, D; Dunowska, M; Stanislawek, WL; Spence, RP; McDonald, WL; Munro, G; et al.
Abstract: CASE HISTORY AND CLINICAL FINDINGS: On 9 January 2014 (Day 0) a mare from a stud farm in the Waikato region presented with urinary incontinence without pyrexia. Over the following 33 days 15 mares were clinically affected with neurological signs. All but one mare had a foal at foot. The most commonly observed clinical signs were hind limb paresis and ataxia. In some cases recumbency occurred very early in the course of disease and seven mares were subject to euthanasia for humane reasons. LABORATORY FINDINGS: Equid herpesvirus (EHV) type 1 was detected using PCR in various tissues collected post mortem from two mares with neurological signs. DNA sequencing data from the DNA polymerase gene of the virus showed a nucleotide transition at position 2254, a mutation encoding amino acid D752 that is highly associated with the neuropathogenic genotype of EHV-1. In total 12/15 mares were confirmed positive for EHV-1 on PCR. Results from a virus neutralisation test and ELISA on paired serum samples, and PCR on whole blood and nasal swabs, indicated that of four paddocks in a high-risk area where a cluster of cases had occurred, 20/21 (95%) horses were likely to have been exposed or were confirmed infected with EHV-1. Subsequent to the outbreak two mares aborted, one at 9 months and one at 10 months of gestation. The cause of abortion was confirmed as EHV-1 with the same genotype as that involved in the outbreak. DIAGNOSIS: Equine herpesvirus myeloencephalopathy. CLINICAL RELEVANCE: The outbreak described shows the considerable impact that can occur in outbreaks of equine herpesvirus myeloencephalopathy in New Zealand. Early biosecurity controls not only reduced the effect on the farm but mitigated the potential for the virus to spread to other horse enterprises.